THE USE OF CRITICAL DEBATE TECHNIQUE TO IMPROVE THE SPEAKING SKILL OF THE SIXTH SEMESTER STUDENTS OF IAI HAMZANWADI NW AT PANCOR - Syamsul Rizal; Azhari Fathurrohman (Prodi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah IAI Hamzanwadi NW Pancor, 2019)
The teaching of English as a Foreign Language (EFL) speaking is necessary for university students to have basic skills of oral communication. Using critical debate technique in the teaching of EFL speaking might be beneficial to help students improve their speaking skills. As critical debate is a medium where the students can train their argumentative competence in form of debating process that demands them to communicate their opinions, argumentations, statements, and other substances, which support their position in the debate process. The aim of this research was to investigate the use of critical debate technique to improve the speaking skill of the sixth semester students of IAIH NW at Pancor. Based on the data of preliminary study, it was found that the students encountered many problems in their speaking class such as; the students had low motivation and reticence to speak, poor grammar and vocabulary, and had some errors in pronunciation. With regard to the problem, this classroom action research was conducted to solve those problems occurring in the speaking class. This research was a collaborative action research in which a collaborator assisted the researcher to collect the data using speaking scoring rubric, questionnaire and field notes. This research was conducted in two cycles focusing on the improvement of the students’ speaking performance and their positive attitude to the implementation of critical debate technique in the speaking class. After the implementation of critical debate technique in the speaking class for two cycles, it revealed that the use of critical debate technique could improve the students’ speaking performance and give them positive attitude to the implementation activities. The findings showed that the average score of the students’ speaking performance could achieve 85.11 from the determined score 75. In addition, it was also found that 84.13 % of the students had positive attitude to the implementation of the use of critical debate technique in the speaking class. The implementation of the use of critical debate technique in speaking class can cover a procedure of three main phases: The first phase is to speak out, second listen to different kinds of opinions and the third at the end respecting those differences. Based on the findings, it is concluded that the use of critical debate technique can be one of the solutions to improve not only the students’ speaking skills but also the their’ positive attitude in the teaching of speaking. Therefore, English teachers are suggested to use critical debate technique to teach their students in speaking class.